Mycotoxins as antinutritional factors: occurrence, impacts and management - Alexandra C. Weaver (Journal of Applied Poultry Research)
Summary: Mycotoxins are chemical metabolites produced by a variety of mold species. While mycotoxin form and concentration can vary from year to year, by location and by feedstuff type, mycotoxins are a contaminant that has global reach and has potential to influence the health of both animals and humans. In poultry, the negative effects of mycotoxins may be observed through changes in growth performance and efficiency, damage to internal organs, alterations in nutrient and mineral status, changes to hormone regulation and reproduction, and impaired immune function which could result in poor vaccination response or increased disease occurrence. Together, these effects lead to an overall reduction in production performance and bird health. Given the chemical nature of mycotoxins and their negative effects on birds, mycotoxins are similar to another category of compounds called antinutritional factors. These compounds are also metabolites, in this case produced by plants, that can result in adverse effects when consumed by birds. Attention has been given to antinutritional factors by poultry producers and nutritionists, and mycotoxins certainly deserve the same level of concern. However, through analysis of feedstuffs and feeds, understanding of mycotoxin risk, and proper management techniques, producers have the ability to mitigate the challenges posed by mycotoxins.